2014
DOI: 10.1021/jp5028838
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants of Expansivity of Native Globular Proteins: A Pressure Perturbation Calorimetry Study

Abstract: There is a growing interest in understanding how hydrostatic pressure (P) impacts the thermodynamic stability (ΔG) of globular proteins. The pressure dependence of stability is defined by the change in volume upon denaturation, ΔV = (∂ΔG/∂P)T. The temperature dependence of change in volume upon denaturation itself is defined by the changes in thermal expansivity (ΔE), ΔE = (∂ΔV/∂T)P. The pressure perturbation calorimetry (PPC) allows direct experimental measurement of the thermal expansion coefficient, α = E/V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
(85 reference statements)
0
8
0
Order By: Relevance
“…Interestingly, the magnitude of the negative expansivities for the nonpolar amino acid side chains is not proportional to their hydrophobicity, but correlates with the size of side chain [1]. Formerly, it was believed that proteins owing relatively high numbers of hydrophilic side chains would cause higher a-values [2], but recent studies using mutations of the surface groups of proteins indicate that the a-values of these proteins were not significantly affected [7,8]. In contrast to the native state of proteins, expansivities of unfolded proteins are more strongly dependent on the nature of the exposed atomic groups and can be empirically estimated based on the contributions of the individual side chains [9].…”
Section: Expansivity and Hydration Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the magnitude of the negative expansivities for the nonpolar amino acid side chains is not proportional to their hydrophobicity, but correlates with the size of side chain [1]. Formerly, it was believed that proteins owing relatively high numbers of hydrophilic side chains would cause higher a-values [2], but recent studies using mutations of the surface groups of proteins indicate that the a-values of these proteins were not significantly affected [7,8]. In contrast to the native state of proteins, expansivities of unfolded proteins are more strongly dependent on the nature of the exposed atomic groups and can be empirically estimated based on the contributions of the individual side chains [9].…”
Section: Expansivity and Hydration Propertiesmentioning
confidence: 99%
“…A similar PPC study on various genetically engineered mutant proteins supported the exclusion of other possible contributing factors to the expansivity of the native proteins, such as the amount of secondary structural elements, the packing density, dynamics and surface electrostriction. Based on these results, it has been hypothesized that the intrinsic network of interactions that defines the tertiary fold is largely responsible for the native protein's expansivity values and its temperature dependence [8]. Further studies are needed to confirm these findings and to clarify the possible correlation between protein topology and expansion of the folded state as a function of temperature, however.…”
Section: Temperature Dependence Of the Volume Change Of Unfoldingmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the thermal expansion coefficient for the native state a N (T) also shows nonlinear dependence on temperature, although this dependence is not as steep as for the unfolded state, particularly in the temperature range between 0°C and ~60°C (see ref [38] and case studies below).…”
Section: Temperature Dependence Of Thermal Expansion Coefficients Of mentioning
confidence: 96%
“…The second important factor is that the amino acid substitutions have little effect on the α N (T). In an extensive study of over nine different proteins and several of their variants, we have shown that α N (T) appears to be defined by the topology of a given protein fold [38]. Thus one can use the estimated α N (T) of a more stable variant to fit the data of a less stable one.…”
Section: Case Study 2: Acp and Variantsmentioning
confidence: 99%